The association between conventional and dynamic control knee strength ratios in elite soccer players - Ruas, C. V.; Pinto, M. D.; Brown, L. E.; Minozzo, F.; Mil-Homens, P.; Pinto, R. S. (Isokinetics and Exercise Science, 2015)
BACKGROUND: The isokinetic hamstrings to quadriceps (H:Q) dynamic control ratio (DCR) is frequently used to assess muscle imbalances and to screen for potential risks of knee injuries in sports. OBJECTIVE: To investigate the correlation between knee conventional ratio (CR) and DCR in elite soccer players and check for a possible relationship. A positive correlation would indicate that the CR could predict DCR. METHODS: One hundred and thirteen Brazilian elite soccer players (25.2 ± 5.3 yrs) performed maximal dominant and nondominant knee concentric (CON) and eccentric (ECC) strength tests at 60°/s on an isokinetic dynamometer in order to calculate CR and DCR. RESULTS: A significant positive correlation between ratios was found for the dominant and non-dominant knees (r=0.54 and 0.62; p < 0.001 which translated into low R^{2} values of 0.29 and 0.39, respectively. CONCLUSION: This suggests that the CR may not replace the DCR and is thus of a limited clinical value in assessing knee muscles imbalance. On the other hand, the paper presents for the first time a robust reference frame for the isokinetic strength and related ratios of the two major knee muscles in soccer players. ABSTRACT FROM AUTHOR